The effect of postoperative anticoagulation on acute aortic dissection: a systematic review and meta-analysis - Gong, Xiangfeng; Lang, Qianlei; Qin, Chaoyi; Meng, Wei; Xiao, Zhenghua (Frontiers in Cardiovascular Medicine, 2023)
Background and aim The evolution of the false lumen after the repair of acute aortic dissection has been linked to numerous adverse clinical outcomes, including increased late mortality and a higher risk of reoperation. Despite the widespread use of chronic anticoagulation in patients who have undergone repair for acute aortic dissection, the effects of this therapy on false lumen evolution and its subsequent consequences are yet to be fully understood. This meta-analysis aimed to investigate the impact of postoperative anticoagulation on patients with acute aortic dissection. Methods In PubMed, Cochrane Libraries, Embase, and Web of Science, we performed a systematic review of nonrandomized studies, comparing outcomes with postoperative anticoagulation vs. non-anticoagulation on aortic dissection. We investigated the status of false lumen (FL), aorta-related death, aortic reintervention, and perioperative stroke in aortic dissection patients with anticoagulation and non-anticoagulation. Results After screening 527 articles, seven non-randomized studies were selected, including a total of 2,122 patients with aortic dissection. Out of these patients, 496 received postoperative anticoagulation while 1,626 served as controls. Meta-analyses of 7 studies revealed significantly higher FL patency in Stanford type A aortic dissection (TAAD) postoperative anticoagulation with an OR of 1.82 (95% CI: 1.22 to 2.71; Z = 2.95; I²=0%; P = 0.93). Moreover, there was no statistically significant difference between the two groups in aorta-related death, aortic reintervention, and perioperative stroke with an OR of 1.31 (95% CI: 0.56 to 3.04; Z = 0.62; I² = 0%; P = 0.40), 0.98 (95% CI: 0.66 to 1.47; Z = 0.09; I² = 23%; P = 0.26), 1.73 (95% CI: 0.48 to 6.31; Z = 0.83; I² = 8%; P = 0.35), respectively. Conclusions Postoperative anticoagulation was associated with higher FL patency in Stanford type A aortic dissection patients. However, there was no significant difference between the anticoagulation and non-anticoagulation groups in terms of aorta-related death, aortic reintervention, and perioperative stroke.